Relaxin in fibrotic ligament diseases: Its regulatory role and mechanism - Yuan, Shuai; Guo, Dong; Liang, Xinzhi; Zhang, Luhui; Zhang, Qun; Xie, Denghui (Frontiers in Cell and Developmental Biology, 2023)
Fibrotic ligament diseases (FLDs) are diseases caused by the pathological accumulation of periarticular fibrotic tissue, leading to functional disability around joint and poor life quality. Relaxin (RLX) has been reported to be involved in the development of fibrotic lung and liver diseases. Previous studies have shown that RLX can block pro-fibrotic process by reducing the excess extracellular matrix (ECM) formation and accelerating collagen degradation in vitro and in vivo. Recent studies have shown that RLX can attenuate connective tissue fibrosis by suppressing TGF-β/Smads signaling pathways to inhibit the activation of myofibroblasts. However, the specific roles and mechanisms of RLX in FLDs remain unclear. Therefore, in this review, we confirmed the protective effect of RLX in FLDs and summarized its mechanism including cells, key cytokines and signaling pathways involved. In this article, we outline the potential therapeutic role of RLX and look forward to the application of RLX in the clinical translation of FLDs.